Contemporary urbanization in the Brazilian Amazon: food markets, multisited households and ribeirinho livelihoods - Tatiana Schor; Gustavo S. Azenha; Estevan Bartoli (Confins)
The past decade witnessed important changes in the Amazon region. The diversity of cities and urbanization processes has shown that it is inadequate to envision urbanization as a singular process. Rather, urbanization needs to be understood as a variety of processes and with a multitude of complex consequences. In order to understand this emergent and complex urbanization in the Amazon the topic of urbanization has to be critically discussed and the unique nuances that characterize contemporary dynamics between rural and urban spaces in Amazonia must be understood. Food is a means to provide insights into the nuances of ribeirinho social, economic, spatial, and environmental dynamics. Thus the analysis of contemporary ribeirinho food acquisition and consumption practices, gives special attention to the important role of roving riverine markets in food regimes, which serve as a connective tissue in the Amazon, linking settlements throughout the region socially, economically, and environmentally. Clearly there has been a reconfiguration and strengthening of the urban network and the Urban-Ribeirinho Territorial System in the Amazon has changed consumptive and productive practices that characterize ribeirinho livelihoods. These changing practices have important implications for land use and agricultural/extractive activities central for the understanding of urbanization in the Brazilian Amazon.